Assessment of Fear of Failure Among Medical Students at King Saud University - Alabduljabbar, Abeer; Almana, Lyan; Almansour, Alanoud; Alshunaifi, Aljoharah; Alobaid, Nada; Alothaim, Norah; Shaik, Shaffi Ahamed (Frontiers in Psychology, 2022)
Background: Fear of failure (FoF) is described as “dispositional tendency to avoid failure in achievement settings”. It may potentially adversely affect students' ability to perform well in their educational activities. Objectives: To measure FoF among medical students at King Saud University, compare FoF between males and females, academic levels, grade point-average (GPA) and other factors among medical students. Method: A cross-sectional observational study was carried out using Stratified Random Sampling. A total of 455 medical students completed “The Performance Failure Appraisal Inventory” during the academic year 2019-2020 at King Saud University, Riyadh, Saudi Arabia. Results: The results showed that the mean of FoF was -0.3117. Moreover, higher levels of fear of devaluing one’s self estimate were seen in females and higher levels of fear of important others losing interest were seen in males. A significant relation was seen between different academic levels and fear of shame and embarrassment, fear of upsetting important others, as well as FoF. High levels of FoF were seen in those who had a GPA below 3.5 and a GPA greater than 4.9, also it was high in students who have no interest in studying medicine. The Cronbach’s α value of all items 0.93 indicates the good internal consistency and factor analysis confirms 5 items of an instrument. Conclusion: The overall level of FoF was low among medical students in King Saud University. However, the domains and levels of FoF differed significantly according to gender, academic level, GPA and the interest in studying medicine.